2003
DOI: 10.1002/yd.53
|View full text |Cite
|
Sign up to set email alerts
|

Connected in Seattle? An exploratory study of student perceptions of discipline and attachments to teachers

Abstract: How do students' perceptions about their treatment in school differ along racial and gender lines?

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 5 publications
0
9
0
Order By: Relevance
“…A common method for calculating representation and determining disproportionality is the composition index (Donovan & Cross, 2002; Skiba et al, 2011) which is calculated by comparing the proportion of students identified for special education in one demographic group with the proportion of students of the same demographic group within the entire student population (Wald & Kurlaender, 2003). For example, to determine the composition index of American Indian students, researchers calculate the percentage of American Indian students in the sample and compare it with the percentage of American Indian students who were identified for special education services in that same sample.…”
Section: Determining Disproportionalitymentioning
confidence: 99%
See 1 more Smart Citation
“…A common method for calculating representation and determining disproportionality is the composition index (Donovan & Cross, 2002; Skiba et al, 2011) which is calculated by comparing the proportion of students identified for special education in one demographic group with the proportion of students of the same demographic group within the entire student population (Wald & Kurlaender, 2003). For example, to determine the composition index of American Indian students, researchers calculate the percentage of American Indian students in the sample and compare it with the percentage of American Indian students who were identified for special education services in that same sample.…”
Section: Determining Disproportionalitymentioning
confidence: 99%
“…There is no universally accepted percentage that indicates underrepresentation or overrepresentation (Wald & Kurlaender, 2003), in fact, underidentification and overidentification criteria are determined by individual states and as a result may vary widely from one state to the next and may change annually (NEA/NASP, 2007;USDOE, 2007). For example, schools in the districts of Louisiana are considered to have overrepresentation if students in a particular group are identified at twice the rate of other students in an academic year, while schools in the districts of Nebraska are considered to have overrepresentation if students in a particular group are identified at three times the rate of other student in two consecutive academic years (U.S. Government Accountability Office, 2013).…”
Section: Determining Disproportionalitymentioning
confidence: 99%
“…Due to evidence of disparate outcomes for students enrolled in behavior-focused and academic remediation-focused alternative schools, this disproportionality is especially concerning. Furthermore, students removed from traditional, general education settings and relocated to more restrictive and segregated placements for reasons related to poor behavior are at increased risk for school disengagement, dropout, and psychosocial effects such as feelings of alienation, depression, and worthlessness (Brown, 2007;Chapin & Griffin, 2005;Redding et al, 2005;Sekayi, 2001;Wald & Kurlaender, 2003;Wald & Losen, 2003). Many of these experiences, such as dropping out and depression, have negative lifelong implications on an individual's employability, family dynamics, and association with judicial systems such as juvenile corrections or prison (e.g., Sum, Khatiwada, McLaughlin, & Palma, 2009).…”
Section: Race/ethnicity Across School Typementioning
confidence: 99%
“…It is important to determine not only why these students are being overreferred and excluded from educational settings but also what educators can do to prevent further overrepresentation as they develop and progress in the public education system. Past researchers have noted the difficulty in determining the causes for differing ODR rates (e.g., Wald & Kurlaender, 2003), which is why it may be beneficial to conduct qualitative studies at individual school sites.…”
Section: Implications For Practice and Researchmentioning
confidence: 99%